2005
DOI: 10.1210/en.2004-1239
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Posttranscriptional Regulation of Fibulin-1 by Estrogens Leads to Differential Induction of Messenger Ribonucleic Acid Variants in Ovarian and Breast Cancer Cells

Abstract: Fibulin-1 is an extracellular matrix protein overexpressed in epithelial ovarian and breast cancers. In estrogen receptor (ER)-positive ovarian and breast cancer cell lines, fibulin-1 mRNA levels are markedly increased by estrogens. Transfection experiments using fibulin-1 promoter constructs indicate that 17beta-estradiol (E2) increases fibulin-1 gene transcription and that ERalpha is more potent than ERbeta to mediate E2 regulation of the transfected fibulin-1 promoter. Using SL2 cells devoid of specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 57 publications
3
38
0
1
Order By: Relevance
“…In ER-positive ovarian and breast cancer cell lines, fibulin-1 mRNA levels are markedly increased by estrogens. Transfection experiments using fibulin-1 promoter constructs demonstrated that E 2 increases fibulin-1 gene transcription and that ERa is more potent than ERb to mediate E 2 regulation of the transfected fibulin-1 promoter (Bardin et al 2005). In our study, fibulin-1 was identified among genes down-regulated by E 2 in leukocytes and this finding was consistent when validated with real-time PCR.…”
Section: Discussionsupporting
confidence: 86%
“…In ER-positive ovarian and breast cancer cell lines, fibulin-1 mRNA levels are markedly increased by estrogens. Transfection experiments using fibulin-1 promoter constructs demonstrated that E 2 increases fibulin-1 gene transcription and that ERa is more potent than ERb to mediate E 2 regulation of the transfected fibulin-1 promoter (Bardin et al 2005). In our study, fibulin-1 was identified among genes down-regulated by E 2 in leukocytes and this finding was consistent when validated with real-time PCR.…”
Section: Discussionsupporting
confidence: 86%
“…14 Fibulin1C mRNA expression can be induced by estrogen in estrogen receptor ␣-positive ovarian tumor cell lines, 14,32 and overexpression of fibulin-1C mRNA in ovarian cancer has been associated with tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…for hormone-induced transactivation in breast cancer and other cell lines (Porter et al 1996, Duan et al 1998, Sun et al 1998, 2005, Qin et al 1999, Xie et al 1999, 2000, Byrne et al 2000, Salvatori et al 2000, Saville et al 2000, Stoner et al 2000, Tanaka et al 2000, Castro-Rivera et al 2001, Li et al 2001, Bruning et al 2003, Jacobson et al 2003, Khan et al 2003, Ngwenya & Safe 2003, Schultz et al 2003, 2005, Fujita et al 2004, Bardin et al 2005, Zhao et al 2005, Higgins et al 2006b. In this study, we have also used RNA interference and small inhibitory RNAs (siRNAs) for Sp1 (iSp1), Sp3 (iSp3), and Sp4 (iSp4) to investigate the role of individual Sp proteins in ERa/Sp-mediated transactivation in MCF-7 cells.…”
Section: Role Of Sp Proteins Of Hormonal Activation Of Psp1mentioning
confidence: 99%
“…For example, studies in this laboratory and others have demonstrated that deletion and mutational analysis of promoters derived from several E 2 -responsive genes contain GC-rich motifs that bind Sp proteins (Safe & Kim 2004). Some of the genes that fall into this category are important for cell proliferation, angiogenesis, and nucleotide metabolism and include E 2 F1, retinoic acid receptor a (RARa), carbamoylphosphate synthetase/ aspartate transcarbamylase/dihydroorotase (CAD), bcl-2, DNA polymerase a, vascular endothelial growth factor (VEGF), VEGFR receptor 2 (VEGFR2), progesterone receptor, creatine kinase B, thymidylate synthase, insulinlike growth factor binding protein 4, epidermal growth factor receptor, receptor for advanced glycation end products, low density lipoprotein receptor, vitamin D receptor, pS2, LRP16, metastasis associated protein 3, and SK3 (Porter et al 1996, Duan et al 1998, Sun et al 1998, 2005, Qin et al 1999, Xie et al 1999, 2000, Byrne et al 2000, Salvatori et al 2000, Saville et al 2000, Stoner et al 2000, Tanaka et al 2000, Castro-Rivera et al 2001, Li et al 2001, Bruning et al 2003, Jacobson et al 2003, Khan et al 2003, Ngwenya & Safe 2003, Schultz et al 2003, 2005, Fujita et al 2004, Bardin et al 2005, Zhao et al 2005, Higgins et al 2006b). In addition, RNA interference studies with a small inhibitory RNA (siRNA) for Sp1 (iSp1) show that after transfection with iSp1, there was a significant decrease in hormone-induced G 0 /G 1 to S-phase progression, suggesting that ERa/Sp1 plays an important role in this process (Abdelrahim et al 2002).…”
Section: Introductionmentioning
confidence: 99%